Comprehensive Evaluation of Urban Renewal Based on Entropy and TOPSIS Method: A Case of Shandong Province - Ziqi Qiao; Xiang Xu; Xinran Wang; Yifen Zhang (Alanya Üniversitesi, 2025)
This study offers a comprehensive evaluation of urban renewal efforts in Shandong Province, China, by employing the entropy method combined with the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS). An evaluation index system was constructed to assess the weights of key factors influencing urban renewal, including the renovation of old residential areas, improvement in sewage treatment quality, development of sponge cities, adoption of clean heating, and enhancement of air quality. Analysis of 16 prefecture-level cities in 2019 reveals significant disparities in performance, with Jinan achieving the highest ranking due to notable improvements in infrastructure and environmental management. Meanwhile, other cities displayed varying levels of success, reflecting different developmental stages and capacities. The findings underscore the necessity for tailored strategies to optimize urban renewal outcomes, focusing on high-weight factors such as sewage treatment, clean heating, and residential renovation. This study provides actionable insights for policymakers, advocating adaptive renewal strategies that align with local contexts and encourage continuous innovation. The results highlight the importance of targeted policy interventions to enhance urban renewal quality across Shandong Province, promoting sustainable urban development and better living standards.